Pengaruh Fasilitas Kerja Terhadap Kinerja Pegawai - Adhie Fasha Nurhadian (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2019)
This study aims to determine the effect of work facilities on employee performance. The important role of work facilities can be divided into two aspects namely physical and non-physical facilities to facilitate organizational activities. The research method used is a verification method. The sample used is an employee at one of the government agencies in Bandung Regency. Data analysis techniques using path analysis. The results of the study prove that there is an influence of physical and non-physical facilities on the performance of 67.9%.